Standard Javanese Causatives in online editorials and short stories - Noor Malihah (IAIN Salatiga, 2014)
This paper explores the distinctive features of the standard Javanese causatives in on-line editorials and short stories. This research is based on written corpus. This written corpus was compiled from articles published in an online newspaper Solo Pos. To analyze the corpus, I have developed a system of manual annotation to identify the features of verb transitivity, the animacy and humanness of the verb, the presence of active, passive and ergative-like clauses and the number of other grammatical and semantic features using a system of tags. Using this annotation, I analyze the data based on dua anlaysis: genre analysis, functional analysis using a quantitative method. The findings show that genre influences the selection of causative types (markers). Also, there exists gawe used as a verb of causation in both editorials and short stories which contradicts to the canonical rule of the Javanese active verb and Malihah’s (2014) findings. The finding also shows that the standard Javanese causative in online editorials and short stories occurs with intransitive verbs. The last finding is that active clause is the relative prominent type of clause which occurs in all marker. In conclusion, the above findings have made contributions to knowledge to Javanese grammar.Keywords: Javanese; causatives; causation types; genre